Precise Preparation of Various Morphological Silver Sulfide Nanostructures, Investigation of Formation Mechanism, and Comparative Study of Photothermal Performance for Cancer Treatment. (16th December 2021) - Gao, Minjie; Du, Jiyuan; Han, Zehua; Wang, Zhihua; Zhao, Yanbao; Zou, Xueyan; Sun, Lei
Abstract: As a bio‐nanomaterial with low toxicity, Ag2 S has attracted more and more attention due to its intensive absorption of near‐infrared (NIR) light. Meanwhile, it has become a novel and excellent photothermal transduction agent due to its local surface plasma resonance effect. However, little research is conducted with respect to the influences of factors such as shapes on photothermal property. In this paper, a novel and convenient strategy is proposed to prepare three shapes of Ag2 S (i.e., hollow nanospheres, nanoplates, and porous nanoplates), and their formation mechanisms are revealed through various characterizations. Furthermore, the in vitro capabilities of hollow Ag2 S nanospheres are compared with nanoplates and porous nanoplates as photothermal transduction agents for theranostic applications. All these Ag2 S nanostructures can absorb and convert 808 nm NIR light into heat. Among them, porous Ag2 S nanoplates possess the highest photothermal conversion efficiency, whereas hollow Ag2 S nanospheres have the maximum temperature difference. In addition, hollow Ag2 S nanospheres exhibit the highest cellular uptake and the best treatment effect. Combined, it can be concluded that hollow Ag2 S nanospheres are promising candidates for cancer treatment. Abstract : Various morphological Ag2 S nanostructures are prepared via a novel and convenient strategy. Their formation mechanisms are revealed and their photothermal properties are investigated. The relationship between morphology and photothermal property is revealed. Hollow Ag2 S nanospheres exhibit the optimal photothermal therapy efficacy in vitro.